ON THE ENERGY OF p-SEMISHADOW AND p-NEW DUPLICATE GRAPH: Investigating Adjacency Energy in Several Graph Operations - shalsabilla, Az Zahra; ALGHOFARI, ABDUL ROUF; HIDAYAT, NOOR (Jurnal Matematika UNAND, 2025)
Graph is mathematical structures used to represent relationships between objects as a vertex and edge (relationship between vertices). The energy of the graph is the absolute sum of the eigenvalues of its adjacency matrix, the graph representation matrix with entries 1 and 0. This article introduces a new graph operation, p-new duplicate, and determines energy of p-semishadow and p-new duplicate.